Evaluasi status faali tiroid daerah gondok endemic kecamatan sawangan, kabupaten magelang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRAK The thyroid status of apparently euthyroid women from an endemic goiter area, the Sawangan Sub-district, and a non endemic goiter area, the Mungkid Sub-district, Magelang District were examined. The study subjects were child-bearing-age women, who were not pregnant nor lactating. Total Ti, total T3, TSH and TBG of both groups were determined by the RIA method. Albumin and haemoglobin concentrations were measured as nutrional status parameters. The findings were as follows : 18 (10.8%) showed hyperthyroidism, 87 (52.4%) were euthyroid and 61 (36.8%) indicated hyperthyroidism. Of the latter 18 (10.8%) showed primary hyperthyroidism, 21 (12.7%) secondary hyperthyroidism and 22 (13.3%) subclinical hyperthyroidism. The concentration of albumin in the endemic area was 3.4 ± 1.0 g/dl, which was statistically different (p < 0.05) from that of the non endemic area (3.8 ± 1.2 g/dl). The concentration of haemoglobin in the endemic area was 12.5 ± 2.4 g/dl, which was not significanly different (p